Cleric Depoliticization of the NU Pesantren in Former Karesidenan Surakarta at the New Order Era (1971-1997) - Alam, Muhammad Bagus Sekar; Warto, Warto; Setiasih, Insiwi Febriary (History Department, Semarang State University and Historian Society of Indonesia, 2021)
The study aims to explain the dynamics of the political life of NU pesantren ulama (clerics) in the Former Karesidenan Surakarta during the New Order era (1971-1997). The New Order regime attempted to maintain power and created political stability tends to use a repressive approach. One of the social groups that gained political pressure from the New Order regime was the NU pesantren ulama. The New Order Government assessed them as an interested social group seeking to uphold Islamic law and anti-government policy. NU pesantren ulama had experienced political pressure in the various situation in the Former Karesidenan Surakarta. It started from the regulations (Permen No. 12 the Year 1969 and PP No.6 the Year 1970) to the act of political intimidation ahead of the New Order election. From 1971 to the 1997 election, the New Order Regime tried to marginalize the NU Pesantren Ulama’s political role at the grassroots level. The New Order’s repressive policies made NU pesantren ulama in former Karesidenan Surakarta did some acts of experimentation to save the NU Organization and their NU pesantren survival. One of their activities is through the Khittah NU 1984, which provided personal freedom for NU pesantren ulama to choose their political affiliation. The conclusion of this paper shows that the New Order Government is an anti-political party regime that is ruling with an authoritarian approach.Tulisan ini menjelaskan dinamika kehidupan politik ulama pesantren NU di wilayah eks-Keresidenan Surakarta pada masa rezim Orde Baru tahun 1971-1997. Rezim Orde Baru dalam upaya mempertahankan kekuasaan dan menciptakan stabilitas politik cenderung menggunakan pendekatan represif. Salah satu kelompok masyarakat yang mendapatkan tekanan politik dari rezim Orde Baru adalah ulama pesantren NU. Mereka dinilai Pemerintah Orde Baru sebagai kelompok sosial yang berusaha menegakkan hukum Islam dan anti kebijakan pemerintah. Tekanan politik dalam berbagai situasi telah dialami ulama pesantren NU di wilayah eks-Keresidenan Surakarta. Mulai dari regulasi (Permen No. 12 Tahun 1969 dan PP No.6 Tahun 1970) hingga tindakan intimidasi politik menjelang pemilu-pemilu Orde Baru. Dari Pemilu 1971 sampai Pemilu 1997, rezim Orde Baru berusaha memarjinalkan peran politik ulama pesantren NU di akar rumput. Kebijakan represif Orde Baru ini membuat ulama pesantren NU di wilayah eks-Keresidenan Surakarta sering kali bereksperimentasi politik guna menyelamatkan organisasi NU dan kelangsungan hidup pesantrennya. Salah satunya melalui Khittah NU tahun 1984 yang memberikan kebebasan personal ulama pesantren NU dalam menentukan afiliasi politiknya. Kesimpulan tulisan ini menunjukkan usaha depolitisasi terhadap ulama pesantren NU memperkuat fakta bahwa Pemerintah Orde Baru merupakan rezim anti partai politik yang berkuasa dengan pendekatan otoriter.